2023
DOI: 10.3390/nu15112516
|View full text |Cite
|
Sign up to set email alerts
|

Living Alone: Associations with Diet and Health in the Spanish Young Adult Population

Abstract: Eating together as a family has important health benefits, as the diet is more balanced and of a higher quality. Eating together is also a factor in the prevention of diet-related diseases. The promotion of family and shared meals is currently a public health strategy. The aim of this research was to study the eating habits of the Spanish young adult population and their impact on health. An observational, descriptive, cross-sectional study was carried out using surveys. A questionnaire was designed and valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This same survey also indicates that a higher level of education is associated with a lower BMI, implying greater awareness of the importance of a balanced diet and the potential health risks associated with incorrect or inadequate nutrition [108]. Moreover, it has been observed that living alone or in an arrangement without family connections influences some nutritional patterns and health habits [110], with individuals living with family having a higher BMI than those living elsewhere [111].…”
Section: Discussionmentioning
confidence: 95%
“…This same survey also indicates that a higher level of education is associated with a lower BMI, implying greater awareness of the importance of a balanced diet and the potential health risks associated with incorrect or inadequate nutrition [108]. Moreover, it has been observed that living alone or in an arrangement without family connections influences some nutritional patterns and health habits [110], with individuals living with family having a higher BMI than those living elsewhere [111].…”
Section: Discussionmentioning
confidence: 95%
“…This is important given the steady increase in recent years in Western society in people living alone [50][51][52]. While it has been observed that living outside or away from the family home influences some nutritional patterns and health habits [53][54][55][56], the results seem to indicate that it has little influence on drinking. Perhaps it could be interesting to study, and therefore make a future line of work, whether this behaviour, observed for the young adult population, also holds for the older population, which is generally a population more at risk of suffering the detrimental effects of loneliness and living alone [57][58][59][60].…”
Section: Discussionmentioning
confidence: 97%